Nature of Science as Depicted in Turkish Biology Textbooks - İREZ, OSMAN SERHAT (JOHN WILEY & SONS INC, 2009)
Given the impact of textbooks on learning, this study assesses the five most frequently used secondary school biology textbooks in Turkey to examine the nature and the quality of treatment given to the nature of science. A qualitative oriented approach was employed and ethnographic content analysis was used as the methodological framework for this particular research. Data were analyzed by means of cognitive maps. The investigation revealed a number of serious problems with the way nature of science is portrayed in the textbooks. Science was generally portrayed as collection of facts, not as a dynamic process of generating and testing alternative explanations about nature. The authors of the textbooks often appeared not to understand the processes well enough to explain them to students and therefore presented various misleading and inadequate descriptions regarding scientific enterprise, similar to those revealed by research on science teachers' and students' understandings of science. Furthermore, some important aspects of science were found to be neglected by textbooks. The study discusses the future success of scientific literacy movement in Turkey and has implications for science education, science curriculum, and science teacher education in Turkey and other developing countries. (C) 2008 Wiley Periodicals, Inc. Sci Ed 93:422-447, 2009
Keywords: SCHOOL SCIENCE; TEACHERS CONCEPTIONS; ELEMENTARY TEACHERS; SCIENTIFIC LITERACY; LIFE-SCIENCE; BELIEFS; IMAGES; EPISTEMOLOGY; KNOWLEDGE; IDEAS